PROBLEMATIZING METHODOLOGY IN ACCIDENT PREVENTION IN A SUPPLY AND STERILE SERVICES CENTER - Samuel Spiegelberg Zuge; Stela Maris de Mello Padoin; Crhis Netto de Brum; Caroline Sissy Tronco (Universidade Federal do Paraná, 2012)
This study relates an experience of continued education, based on problematizing methodology, which took place in a supplies and sterile services center. It was undertaken in October 2009 with 18 nursing professionals and eight staff from the sterilizing service. Its first stage was observation of the professionals' work reality, from which emerged the key points related to environmental risks at work. Theorization of these points was carried out through discussion groups, the showing of instructional materials, and other group dynamics. After this stage, strategies for supplying the necessities originating in concrete reality and lastly the knowledge (re)-formulated was applied in orientation of peers. As a result of this experience, it was verified that the application of problematizing methodology rendered possible a new way of thinking, valuing and applying personal knowledge in the unit's daily routines.